Elimination of an intraradicular biofilm composed of Enterococcus faecalis and Candida albicans using a negative apical pressure irrigation system. - Verónica Méndez-González; Marlen Vitales-Noyola; Ana González-Amaro; Carlos Muñoz-Viveros; Francisco Ducoing-Hernández (Universidad de Concepción., 2020)
Endodontic treatment consists of the cleaning and disinfecting the root canal system, which is achieved using adequate mechanical instru-mentation and chemical irrigation. Endodontic microorganisms are present in root canals in the form of a biofilm, and their elimination ensures the success of endodontic treatment. Irrigation is a key factor contributing to the elimination of this intraconduct biofilm, and different irrigator agents and irrigation techniques, such as irrigation with negative apical pressure, a novel automated irrigation mechanism based on suction intraconduct, have been used. In this study, we evaluated the ability of a negative apical pressure system with different concentrations of sodium hypochlorite and durations to reduce the microbial load. Materials and Methods: An intraradicular biofilm composed of Enterococcus faecalis and Candida albicans was generated during twenty-one days of static culture on one hundred mesio-vestibular roots of upper molars with complex curvatures greater than 30°C, and the roots were classified in six groups with different concentrations and contact times of sodium hypochlorite. Subsequently, the reduction in the microbial load was measured with McFarland scale and the enumeration of colony forming units and was evaluated with scanning electronic microscopy. Results: We observed a significant difference in the reduction of the microbial load prior to instrumentation compared with postinstrumentation between the groups treated with 2.25% and 5.25% NaOCl for 30, 60 and 90 seconds of contact time (p<0.05), but we did not observe differences in the reduction of microbial load between different contact times and concentrations of sodium hypochlorite employed (p>0.05). Conclusion: Negative apical pressure is a good option for irrigation in endodontics, as it allows the passage of the irrigation fluid along the total length of the root canal and produces a better antimicrobial effect.